A Contrasted Philosophical Approach to Rig Veda & Upanishads in Indian Thought - Samitharathana, Wadigala (The Journal of International Buddhist Studies College, 2019)
Indian Philosophy has been a powerful determinant of Asiatic thoughts. By even the briefest perusal of Indian Philosophy, one may detect gems of wisdom as bright as any of those to be found in the thought of Ancient Greece. Indeed, even in the most cursory survey, it’s at once evident that the thought stemming from the Vedas and Upanishads composes some of the oldest and most profound of all speculative philosophy. Then Indian Philosophy consists of an extraordinary diversity of philosophical thinking, commencing from rank empiricist materialism to the most transcendental absolute idealism, covering all the intermediate shades of thinking.